TAX COMPLIANCE: SLIPPERY SLOPE FRAMEWORK AND THEORY OF REASONED ACTION APPROACH - Adini, Raisa (Accounting Department,, 2021)
Purpose — This study aims to examine and analyze factors that influence tax compliance using socio-psychological factors.Design/methodology/approach — Tax compliance in this study examined using slippery slope framework and theory of reasoned action approach. This study used quantitative method. The data were harvested through a survey using a questionnaire and analyzed using structural equation modeling in SmartPLS version 2.0.Findings — This study finds that tax compliance is influenced by legitimacy and coercive power of the authority, trust in the authority, and taxpayer’s intention. Practical implications — Tax authorities should retain the power they have to maintain trust in the tax revenue that will improve tax compliance.Originality/value — This study develops the slippery slope framework and refines it using intention as the variable, as described by the Theory of Reasoned Action. Keywords — tax compliance; authority’s power; trust in authorities; intention. Paper type — positive paradigm